2014
DOI: 10.1016/j.jvs.2014.02.046
|View full text |Cite|
|
Sign up to set email alerts
|

Elective endovascular aortic repair conversion for type Ia endoleak is not associated with increased morbidity or mortality compared with primary juxtarenal aneurysm repair

Abstract: Objectives Type 1a endoleak after endovascular aortic repair (EVAR) can be a challenging complication to manage, and due to concerns regarding morbidity and mortality of open surgical conversion (OSC), reports of complex endoluminal salvage techniques are increasing. Despite development of these endovascular remedial strategies, many patients ultimately require OSC. The purpose of this analysis was to determine outcomes of elective open conversion for type 1a endoleak and compare them to elective primary open … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…Similarly, the literature shows that open conversion after EVAR has significantly longer operative times than primary AAA open repair (p ¼ .03). 14 On the other hand, the time needed to complete the proximal anastomosis was a mean of 23 minutes, and no complications related to visceral ischemia were observed within 30 days. Clamp time in this experience was lower than the 43 minutes reported by the large Cleveland Clinic 10 report, where interventions for conversion with suprarenal fixation required significantly longer mean visceral ischemia than those with infrarenal fixation (43 vs. 28 min; p ¼ .039).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Similarly, the literature shows that open conversion after EVAR has significantly longer operative times than primary AAA open repair (p ¼ .03). 14 On the other hand, the time needed to complete the proximal anastomosis was a mean of 23 minutes, and no complications related to visceral ischemia were observed within 30 days. Clamp time in this experience was lower than the 43 minutes reported by the large Cleveland Clinic 10 report, where interventions for conversion with suprarenal fixation required significantly longer mean visceral ischemia than those with infrarenal fixation (43 vs. 28 min; p ¼ .039).…”
Section: Discussionmentioning
confidence: 90%
“…Even if this type of intervention represents a challenging situation for the surgeon, the overall elective 30 day mortality is low in most of the reported series in the literature (0 to <10%). Recently, Scali et al 14 published their experience comparing open elective conversion for type 1A endoleak and primary open repair of juxtarenal aneurysm; in their conclusions there were no differences in the 30 day mortality rates between the two groups (4% for both; p ¼ 1). Mortality in this series at 30 days was 0% in line with that observed in the literature review, 12,15e25 where the overall 30 day mortality after explantation was very low (<2%), with no significant difference when comparing total versus partial explantation.…”
Section: Discussionmentioning
confidence: 96%
“…An important consequence of older generation devices accruing follow-up time and treatment of more difficult anatomies with modern devices may be higher rates of failure 33, 34 . Indeed, the rationale for pursuing this analysis is related to an increasing number of referrals to our own institution for failed EVAR 7 .…”
Section: Discussionmentioning
confidence: 99%
“…In an effort to understand the risk of EVAR conversion, we recently performed a study at the University of Florida where we demonstrated that in an anatomically and physiologically analogous group of elective EVAR-c and PAR patients, similar rates of postoperative morbidity and mortality can be anticipated 7 . While EVAR-c was associated with increased operative complexity, short-term outcomes did not significantly differ when compared to a similar risk group of elective open AAA patients which reflects the results of this analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Using these methods, we have been able to obtain similar outcomes in elective EVAR-c compared with open repair. 27 Unfortunately, the VQI does not collect data that allow exact determination of the conduct of the EVAR-c, the type of device explanted, or whether any endograft was left in situ to corroborate these results.…”
Section: Discussionmentioning
confidence: 99%